Assessing exposure to physical risk factors for work-related musculoskeletal disorders and relevant psychosocial factors among assembly workers in an automotive component assembly plant - Fazilah, Abdul Aziz; Z., Ghazalli; N. M. Zuki, N. M.; Amri, Isfar (Human Factors and Ergonomics Society Malaysia (HFEM), 2017)
Work-related musculoskeletal disorders (WMSDs) are a common health problem throughout the manufacturing industry. Determination of musculoskeletal disorders and its relevant factors are one the most leading basis for ergonomics intervention programs in the automotive industry. This study was aimed to identify the ergonomics physical and psychosocial risk factors in automotive component assembly plant workers. In total ten workers with different job tasks were observed using Quick Exposure Check (QEC) which is an observational instrument, which allows practitioners and workers to assess four key regions of the body. It was found that automotive assembly component assembly plant workers were exposed to many postural problems while performing automotive component assembly task activities. Results of the QEC scores were found to be very high for the worker’s neck, whereas the scores for the worker’s back (in moving) and worker’s shoulder/arm were found to be high. The workers in spot gun welding process in two workstations including panel member rear cross No.1 spot gun welding assembly process (Line 2) as well as workers at the panel roof side inner spot gun welding assembly process suffered from very high levels of WMSDs at all worker’s main body regions except wrist/hand. Meanwhile, the vibration exposure level is high in most of the workstations. In addition, a very high exposure level for stress has been found in the panel member rear cross No.1 spot gun welding assembly process (Line 2) workstation. Musculoskeletal disorders had a high prevalence among workers in this automotive component assembly plant. The physical and psychosocial risk factors were required to be identified and controlled so that the WMSD’s symptoms can be minimized. The results of this study will be applied to a knowledge-based ergonomics risk assessment system development for assembly plant workers in an automotive component manufacturer.